Endothelial dysfunction and vascular disease - Vanhoutte, P.M; Shimokawa, H; Tang, E.H.C; Feletou, M (Acta Physiologica, 2009)
The endothelium can evoke relaxations (dilatations) of the underlying vascular smooth muscle, by releasing vasodilator substances. The best characterized endothelium-derived relaxing factor (EDRF) is nitric oxide (NO). The endothelial cells also evoke hyperpolarization of the cell membrane of vascular smooth muscle (endothelium-dependent hyperpolarizations, EDHF-mediated responses). Endothelium-dependent relaxations involve both pertussis toxin-sensitive Gi (e.g. responses to serotonin and thrombin) and pertussis toxin-insensitive Gq (e.g. adenosine diphosphate and bradykinin) coupling proteins. The release of NO by the endothelial cell can be up-regulated (e.g. by oestrogens, exercise and dietary factors) and down-regulated (e.g. oxidative stress, smoking and oxidized low-density lipoproteins). It is reduced in the course of vascular disease (e.g. diabetes and hypertension). Arteries covered with regenerated endothelium (e.g. following angioplasty) selectively loose the pertussis toxin-sensitive pathway for NO release which favours vasospasm, thrombosis, penetration of macrophages, cellular growth and the inflammatory reaction leading to atherosclerosis. In addition to the release of NO (and causing endothelium-dependent hyperpolarizations), endothelial cells also can evoke contraction (constriction) of the underlying vascular smooth muscle cells by releasing endothelium-derived contracting factor (EDCF). Most endothelium-dependent acute increases in contractile force are due to the formation of vasoconstrictor prostanoids (endoperoxides and prostacyclin) which activate TP receptors of the vascular smooth muscle cells. EDCF-mediated responses are exacerbated when the production of NO is impaired (e.g. by oxidative stress, ageing, spontaneous hypertension and diabetes). They contribute to the blunting of endothelium-dependent vasodilatations in aged subjects and essential hypertensive patients.